Understanding financial statements / Lyn M Fraser; Aileen Ormiston - Fraser, Lyn M.
This text presents the conceptual background and analytical tools necessary to understand and interpret financial statements. The emphasis throughout is on the evaluation of financial statements, and their application to business decision making